Fenomena remaja - Baharudin Ali Masrom; Zaini Ujang, 1965-; Fatini Yaacob (Kuala Lumpur : Arena Ilmu (M), 1992)
Adolescents; sociocultural issues.
In Malay.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on print version record.
Keywords: Teenagers -- Malaysia; Young adults -- Malaysia